Basics of genome editing technology and its application in livestock species. (August 2017) - Petersen, Bjoern
Contents: In the last decade, the research community has witnessed a blooming of targeted genome editing tools and applications. Novel programmable DNA nucleases such as zinc finger nucleases (ZFNs), transcription activator‐like endonucleases (TALENs) and the clustered regularly interspaced short palindromic repeats/Cas9 system (CRISPR/Cas9) possess long recognition sites and are capable of cutting DNA in a very specific manner. These DNA nucleases mediate targeted genetic alterations by enhancing the DNA mutation rate via induction of double‐strand breaks at a predetermined genomic site. Compared to conventional homologous recombination‐based gene targeting, DNA nucleases, also referred to as Genome Editors (GEs), can increase the targeting rate around 10, 000‐ to 100, 000‐fold. The successful application of different GEs has been shown in a myriad of different organisms, including insects, amphibians, plants, nematodes and several mammalian species, including human cells and embryos. In contrast to all other DNA nucleases, that rely on protein–DNA binding, CRISPR/Cas9 uses RNA to establish a specific binding of its DNA nuclease. Besides its capability to facilitate multiplexed genomic modifications in one shot, the CRISPR/Cas is much easier to design compared to all other DNA nucleases. Current results indicate that any DNA nuclease can be successfully employed in a broad range of organisms which renders them useful for improving the understanding of complex physiological systems such as reproduction, producing transgenic animals, including creating large animal models for human diseases, creating specific cell lines, and plants, and even for treating human genetic diseases. This review provides an update on DNA nucleases, their underlying mechanism and focuses on their application to edit the genome of livestock species.